Electromagnetic navigated positioning of the maxilla after Le Fort I osteotomy in preclinical orthognathic surgery cases - Berger, Moritz; Nova, Igor; Kallus, Sebastian; Ristow, Oliver; Eisenmann, Urs; Freudlsperger, Christian; Seeberger, Robin; Hoffmann, Jürgen; Dickhaus, Hartmut (Oral surgery, oral medicine, oral pathology and oral radiology, 2016)
Objectives Inaccuracies in orthognathic surgery can be caused during face-bow registration, model surgery on plaster models, and intermaxillary splint manufacturing. Electromagnetic (EM) navigation is a promising method for splintless digitized maxillary positioning. Study Design After performing Le Fort I osteotomy on 10 plastic skulls, the target position of the maxilla was guided by an EM navigation system. Specially implemented software illustrated the target position by real-time multistage colored three-dimensional imaging. Accuracy was determined by using pre- and postoperative cone beam computed tomography. Results The high accuracy of the EM system was underlined by the fact that it had a navigated maxilla position discrepancy of only 0.4 mm, which was verified by postoperative cone beam computed tomography. Conclusions This preclinical study demonstrates a precise digitized approach for splintless maxillary repositioning after Le Fort I osteotomy. The accuracy and intuitive illustration of the introduced EM navigation system is promising for potential daily use in orthognathic surgery.
Gesehen am 03.05.2018